Обмеженість сучасних моделей ші та потреба в загальному інтелекті - Фесенко, М. Б.; Вітько, О. В. (ХНУРЕ, 2025)
The current artificial intelligence (AI) systems achieve high performance in narrow tasks but lack generalization capabilities inherent to human intelligence. This limitation hinders adaptability and problem-solving in unfamiliar environments without additional training. This paper examines key shortcomings of modern AI models and justifies the need for artificial general intelligence (AGI) capable of flexible learning, logical reasoning, and autonomous adaptation.
Keywords: загальний інтелект; модель AI